Mucinous cystadenoma: A rare entity - Rai, Shalu (Medknow Publications & Media Pvt Ltd, 2013)
Cystadenoma is a rare benign salivary gland tumor that chiefly originates in the minor salivary glands as a cystic growth with papillary projections into the cystic lumen without the lymphoid element. It is further classified into two histopathological variants that have been recognized by World Health Organization as the papillary and the mucinous forms of cystadenoma. Clinically, it is difficult to differentiate from other benign minor salivary tumors and mucous retention phenomenon. Diagnosis is chiefly based on characteristics histological features. It is believed that the salivary gland tumors are difficult to diagnose and interpret because there are varied patterns of presentation. The study of salivary gland disorders has increased in leaps and bounds. The authors report a case of mucinous cystadenoma of the minor salivary gland on the hard palate, which is even rarest of the rarely reported cystadenomas of the minor salivary glands.